Kaposi′s sarcoma: HIV-negative man with isolated penile localization - Soufiane Mellas; Fadl Tazi; Nawfel Mellas; Ouafae Masbah; Kawtar Znati; Afaf Laamarti; Jamal EL Fassi; Hassan Farih (Wolters Kluwer Medknow Publications, 2010)
Kaposi′s sarcoma is the malignant proliferation of the endothelial cell vessels. Its genesis is still unclear; however, it seems to be related to the herpes virus infection (HHV-8). This neoplasia usually affects the lower limbs and the affected persons are mostly from the Mediterranean region. The exclusive penile localization of the Kaposi′s sarcoma in a patient with a negative HIV serologia is exceptional. Our case is of a 73-year old patient with a negative HIV serology presenting an exclusive penile localization of the Kaposi′s sarcoma treated by radiotherapy.